Understanding the Impact of Approved but Unfunded Vaccine Status on Parental Acceptance of an Adjuvanted Seasonal Influenza Vaccine for Infants: Results from the Pediatric Influenza Vaccination Optimization Trial (PIVOT)–III - William A. Fisher; Vladimir Gilca; Michelle Murti; Alison Orth; Hartley Garfield; Paul Roumeliotis; Emmanouil Rampakakis; Vivien Brown; John Yaremko; Paul Van Buynder; Constantina Boikos; James A. Mansi (Vaccines, 2022)
The adjuvanted trivalent influenza vaccine (aTIV) provides enhanced protection against influenza for infants but is not publicly funded (NPF). The objective of this prospective cohort study of parents with children 6 through 23 months of age was to understand how NPF status influences parental perceptions of approved but unfunded vaccines and their intentions to vaccinate. At healthy baby visits, clinicians provided parents with information about influenza and vaccination. Before and after these interactions, a research nurse assessed parents’ intentions to vaccinate their children and their beliefs about the safety, efficacy, and necessity of vaccinating their children with aTIV in both publicly funded (PF) and NPF settings. Overall, 15 community practice clinics (n = 15 physicians) and nine public health clinics (n = 9 nurses) recruited 207 parents. The percentage of parents intending to immunize their children with aTIV decreased from 72% (vaccine PF, free of charge), to 42% (NPF, $25 per dose), to 27% (NPF, $50 per dose). Funding status strongly influenced whether parents perceived immunization with aTIV to be necessary, safe, and effective. Information on influenza and influenza vaccines should be provided to parents routinely to allow for well-informed decisions on the suitability of specific influenza vaccines for their child.